Plaza de mercado polifuncional para el sector noroccidental de Piedecuesta Santander (2021)
The agricultural market has been evolving through new instruments that force farmers and their merchants to be at the forefront and have a new perspective of production, industrialization, emerging technologies and marketing of their products by applying concepts such as production chains where it is The provision of goods and services is necessary from the planting or gestation process of the animal in the case of livestock to its final destination, which is the client and the value chains that offer new parameters for the correct circulation and distribution of their agricultural products, having as order good economic relations with direct and indirect actors and equitable profits.